3 - The Impact of Structural Violence on Women’s Capacity to Fully Participate at Candidate and Electoral Management Levels in Zimbabwe - Katsande, Rosalie; Bunu, Christabel Tapiwa; Mukumbiri, Paidamwoyo; Stewart, Julie (Africa Development, 2024)
This article focuses on ‘hidden’ institutional violence, also known as structural violence, and gender divisions in electoral processes in Zimbabwe. Structural violence occurs when one category of people is accorded an unequal status in relation to other categories of people. The main argument presented in the paper is that, in Zimbabwe, structural violence renders the implementation of gender equality in electoral governance nugatory. Political party structures and systems are designed and conveniently used to exclude women from political participation. The article analyses selected cases involving women’s involvement at the candidate and electoral management level. The study made use of interviews, particularly key informant interviews, and semi- structured interviews, as its main data-gathering methods. Focus group discussions were also utilised. The findings revealed that a myriad of structural and institutionalised constraints prevent women in Zimbabwe from fully participating in political and electoral processes. These institutionalised structures have a disproportionately negative impact on women’s political ambitions compared to men’s. The article concludes that promoting gender equality in the area of politics and decision-making as well as in society as a whole is a long and complex process. Any initiatives to remedy these inequalities must be strategic and long-term oriented.